(untitled) (Journal of the College of Basic Education, 2022)
Two simple and sensitive spectrophotometric methods have been developed for the estimation of Celecoxib in pure and pharmaceutical dosage forms. Method A is based on ion association complex formation of the drug with Methylene Blue . Method B is based on the charge transfer complexation reaction between Celecoxib and iodine. The absorption spectrum of Celecoxib – methylene blue and Celecoxib –iodine reaction products showed absorption peaks at 665 and 511 nm respectively. The systems obeyed the Beer’s law in the range 0.2–1µg/ml for both the methods A and B. The correlation coefficients and the limits of assays detection values were found to be 0.999, 0.37 for (method A) and 0.998, 0.426 for (method B). , respectively. Proposed methods were successfully applied to the quantitative determination of celecoxib in pharmaceutical dosage forms with good accuracy.